HUBUNGAN ANTARA KECANDUAN SMARTPHONE DENGAN KONSENTRASI KERJA KARYAWAN BAGIAN PENERBITAN MAJALAH PADA CV. X DI YOGYAKARTA - Yohanes Susilo; Dewi Handayani Harahap; Eni Rohyati (Jurnal Psikologi, 2024)
This research aims to determine the relationship between smartphone addiction and employee work concentration. The research subjects were employees of the magazine publishing section at CV. Andi Offset Yogyakarta. The research method uses quantitative methods. The data collection method uses scales, namely the smartphone addiction scale and the work concentration scale. Data analysis method using product moment correlation analysis techniques. The research results show that the coefficient value is rxy= 0.097, the significance is 0.612 or above the significance of 0.05. This shows there is no corelation between smartphone addiction and work concentration. The influence of addiction to smartphones has an impact on work concentration of only 0.9% (r2 = 0.009). This value is very small, because almost 100% of work concentration disorders are influenced by other variables. The research results can be concluded that there is no significant relationship between smartphone addiction and employee work concentration.